2022
DOI: 10.1681/asn.2022010080
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcification Score and the Progression of Chronic Kidney Disease

Abstract: Background Elevated coronary artery calcification scores (CACS) are associated with increased cardiovascular disease risk in patients with chronic kidney disease (CKD). However, the relationship between CACS and CKD progression has not been elucidated. Methods We studied 1936 participants with CKD (stages G1-G5 without kidney replacement therapy) enrolled in the KoreaN Cohort Study for Outcome in Patients With CKD. The main predictor was Agatston CACS categories at baseline (0 AU, 1-100 AU, and >100 AU). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“… 32 In patients with CKD, high CAC was associated with an increased risk of adverse kidney outcomes and CKD progression. 33 These studies demonstrate the importance of inter-organ interactions in patients with CKD and the potential involvement of ectopic calcification in the cardiorenal syndrome.…”
mentioning
confidence: 76%
“… 32 In patients with CKD, high CAC was associated with an increased risk of adverse kidney outcomes and CKD progression. 33 These studies demonstrate the importance of inter-organ interactions in patients with CKD and the potential involvement of ectopic calcification in the cardiorenal syndrome.…”
mentioning
confidence: 76%
“…Coronary artery calcification is a well-known indicator of coronary artery atherosclerosis and an established risk factor for CVD [37]. CACS has been reported as a non-invasive and reliable predictive tool for coronary artery calcification and CVD [6,7,37,38]. Previous studies have revealed that activin is closely related to vascular calcification [19].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of death in patients with KT [4,5]. Among the assessment tools, the coronary artery calcification score (CACS), measured using multi-detector computed tomography (MDCT), is a highly specific index for coronary artery atherosclerosis and can predict major cardiovascular events as a surrogate marker [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…As our results revealed, despite the high cost and unsatisfactory operability of CAC evaluation, the presence of CAC was associated with poor clinical outcomes, which is consistent with the results of a recently published study. 35 This finding may be related to the special structure and function of coronary arteries or to the relatively precise assessment method for CAC. Hence, we focused on the CAC-related results.…”
Section: Discussionmentioning
confidence: 99%